2010
DOI: 10.1007/s00415-010-5590-8
|View full text |Cite
|
Sign up to set email alerts
|

Cellular characterization of MPZ mutations presenting with diverse clinical phenotypes

Abstract: Mutations in MPZ, which encodes myelin protein zero (P(0)), may lead to different subtypes of Charcot-Marie-Tooth disease (CMT). The aim of this study was to characterize the cellular manifestations of various MPZ mutations associated with CMT1, Dejerine-Sottas syndrome (DSS) and CMT2, and to correlate their cellular and clinical phenotypes. Nine P(0) mutants associated with CMT1 (P(0)S63F, R98H, R277S, and S233fs), DSS (P(0) I30T and R98C), and CMT2 (P(0)S44F, D75V, and T124M), were investigated. Wild-type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…The mutation results in a loosened repeat structure without a major impact on protein folding. Arg227 might be involved in electrostatic anchoring of the protein to the lipid headgroups – the R227S mutation likely has low impact on ER stress and UPR, as mutated P0 correctly localizes to the plasma membrane (Lee et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The mutation results in a loosened repeat structure without a major impact on protein folding. Arg227 might be involved in electrostatic anchoring of the protein to the lipid headgroups – the R227S mutation likely has low impact on ER stress and UPR, as mutated P0 correctly localizes to the plasma membrane (Lee et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of misfolded PMP22 and MPZ at the ER 19,20 suggests that ERAD dysfunction and subsequent ER stress may be involved in causing demyelinating CMT. Our recent finding that endosome to the cytosol ( Fig.…”
Section: Impairment In the Proteasome And Aggresome-autophagy Pathwaymentioning
confidence: 99%
“…Hayasaka et al (1993) first identified MPZ mutations as the underlying cause of CMT1B, and until recently, more than a hundred MPZ mutations have been reported to be relevant for CMT. Mutations in MPZ are shown to be responsible for a wide range of CMT phenotypes, which could be categorized into early or late onset neuropathy (Shy et al, 2004;Zschüntzschet al, 2009;Lee et al, 2010). Based on the clinical and electrophysiological features, the present family members with the Gly137Asp MPZ mutation was compatible with demyelinating CMT1B neuropathy.…”
Section: Resultsmentioning
confidence: 87%
“…These variable clinical phenotypes are usually associated with specific MPZ mutations, namely different phenotypes by different mutation sites (Lee et al, 2010). Moreover, some MPZ mutations have been associated with divergent types of nerve pathologies and the same mutationsproduce a spectrum of CMT disorders.…”
Section: Introductionmentioning
confidence: 99%